Militant and political experiences in the formation of the Socialist Party of Chile in the greater Concepción area, 1931-1933 - Sáez Muñoz, Francisco; Muñoz Hernández, Raúl (Revista de Historia Social y de las Mentalidades, 2026)
This article analyzes the formation of the Socialist Party of Chile in Concepción between 1931 and 1933, considering the trajectories, actors, and ideologies that converged at its origin. It argues that, within the framework of local political dynamics, the consolidation of socialism in the area was closely linked to the influence of already established parties, the alliances formed with them, and the actions of leaders who facilitated its organization at specific junctures. In this sense, the experience of the Socialist Republic and the 1932 electoral cycle acted as fundamental articulating axes, offering spaces for organizational and discursive experimentation that decisively influenced the subsequent structuring of regional socialism. Through the study of party, regional, and national press, the main political networks of these groups, their spheres of influence, their links with local actors, and the role of the Socialist Republic in this process are examined.
Keywords: Socialist Party of Chile; Concepción; Socialist Republic; Political Culture